Therapeutic vaccination of woodchucks against chronic woodchuck hepatitis virus infection - Hervas-Stubbs, S. (Sandra); Lasarte, J.J. (Juan José); Sarobe, P. (Pablo); Prieto, J. (Jesús); Cullen, J.M. (John M.); Roggendorf, M. (Michael); Borras-Cuesta, F. (Francisco) (Elsevier, 1997)
BACKGROUND/AIMS: Therapeutic vaccination is a new approach to treat patients with chronic hepatitis B virus infection. We have used the woodchuck model to examine the efficacy and safety of this approach. METHODS: Seven woodchucks chronically infected with woodchuck hepatitis virus were immunized with surface antigen from this virus, purified from plasma, in conjunction with a peptide named FIS (encompassing amino acids 106-118: FISEAIIHVLHSR from sperm whale myoglobin), which is recognized by T helper lymphocytes. As controls, two woodchucks chronically infected with woodchuck hepatitis virus were immunized: one with FIS only and the other with surface antigen only. RESULTS: Co-immunization with surface antigen and FIS, but not with FIS or surface antigen alone, induced anti-surface antibodies in 7/7 immunized woodchucks. In the two woodchucks in which the highest titer of anti-surface antibody was elicited, severe liver damage was observed: one died of fulminant hepatitis and the other became seriously ill with hepatic injury and had to be sacrificed. CONCLUSIONS: Co-immunization of chronically infected woodchucks with surface antigen and a peptide recognized by T helper cells produces a good anti-surface antibody response. However, this strategy needs to be optimized before its implementation in humans. Although our experiments are not strictly comparable to vaccination of chronically hepatitis B virus-infected patients with recombinant or plasma-derived vaccines, we believe that precautions should be taken to avoid the risk of severe liver injury when immunizing hepatitis B virus carriers.